Determinants of Integrated Services Post Programme Utilization in Elderly Empowerment in Medan Amplas District - Septiani Nainggolan, Ivena Hotmarina; Gurning, Fitriani Pramita (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
There is an increase in the elderly population at this time, making the morbidity rate in the elderly also increase. In 2021, the number of elderly people who experienced illness in the past month was around 34.48%. Meanwhile, in 2022, the morbidity rate increased to 41.3%, The purpose of this study was to determine the determinants of the use of posyandu programs in empowering the elderly in Harjosari I Village, Medan Amplas District. The method used is a quantitative approach cross-sectional research design by surveying as many as 30 people as representatives of the population by accidental sampling by conducting interviews using online-based questionnaires, after the interview the data was analyzed statistically using univariate, bivariate and multivariate tests with a multi-stage model Analisys model to obtain crude values and adjusted oods ratio with an alpha significance of 5% (p<0.05). The results showed that the greatest influence on the utilization of the posyandu program was a distance of >100 meters with an exp value (B) of 2.56. The conclusion is that overall variables have a significant relationship with the utilization of elderly posyandu services with risks ranging from 1.43 to 2.56 times.